(untitled) (Journal SCIENCEVOLUTION, 2024)
Popular knowledge remains preserved through time, as a cultural heritage that promotes religious faith and community traditions. In this cultural background, Saint Isidore, known as the patron saint of farmers, remains valid after generations as a manifestation of such knowledge, especially in Latin America and Spain. Because of his relevance, even today, this manuscript addresses the life of Saint Isidore, his canonization and his contemporary significance from both an ecclesiastical and a syncretic perspective. Likewise, the need to keep alive this knowledge and traditions for cultural enrichment.